Research Study of the Levels of Human Guidance in the Holy Qur'an: قرآن مجید میں ہدایت ِ انسانی کے مدارج: تحقیقی مطالعہ - Baig, Dr. Hassan; Raza, Dr. Ahmad; Maqsood, Hafsa (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The focus of the Holy Qur'an is human being, and it fulfills the guiding of humans. Humans who have the honor of being the best of creation, who hold the honor of being the first inhabitant of Paradise, the one who has decorated his head with the crown of being the best among all creations has been given the title of (احسن تقویم) by the Lord of the Worlds. The Creator of the universe has also arranged his guidance. Therefore, when human was placed on earth, Allah's guidance and guidance did not leave him alone. Allah said: "When a message of guidance comes to you from me, whoever follows this guidance, such fortunate souls will not have any fear, nor will they be sad." In this verse, a message has been given to man that worldly and hereafter success and achievement of success and prosperity lies only in obeying and following the guidance of the Lord. The various stages of divine guidance have been described by Allah in the Holy Qur'an. It is the responsibility of humans to follow these stages and obtain complete guidance. Therefore, in this paper, these stages of guidance have been described in the light of the Quranic teachings so that human can progress towards eternal success. Become deserving of eternal blessings of Allah Almighty.